![\begin{gathered} -5x+y=\rightarrow-8-41i \\ x\cdot2y=\rightarrow58+106i \\ -x\cdot y=\rightarrow-29-53i \\ 2x-3y=\rightarrow-15+19i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wuaf256ygmkyxsfphb3c7spjz8m86hjn76.png)
Step-by-step explanation
Let
![\begin{gathered} x=3+8i \\ y=7-i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6rt1ca22n2zmyidzskg2yys3hsq1tioj6l.png)
now, to multiply a imaginary number, multiply the constant
and when adding or subtracting another number, just ad/sub component to component
so
Step 1
a)-5x+y
![\begin{gathered} -5x+y \\ replace \\ -5(3+8i)+(7-i)=\mleft(-15-40i\mright)+\mleft(7-i\mright) \\ -5x+y=(-15+7)+(-40i-i) \\ -5x+y=-8-41i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2uwcipy7jv9rn0mivg58890050jcfkxo1i.png)
Step 2
b)x*2y
![\begin{gathered} x\cdot2y=(3+8i)\cdot2(7-i) \\ x\cdot2y=(3+8i)\cdot(14-2i) \\ x\cdot2y=(3\cdot14)+(3)(-2i)+(8i)(14)+(8i)(-2i) \\ x\cdot2y=42-6i+112i-16(i^2) \\ x\cdot2y=42-6i+112i-16(-1) \\ x\cdot2y=42-6i+112i+16 \\ \text{add like terms} \\ x\cdot2y=58+106i \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d8b6zdggf0hgbb0mathsdygh48awu7mur0.png)
Step 3
c)-x*y
![\begin{gathered} -x\cdot y=-(3+8i)\cdot(7-i) \\ -x\cdot y=(-3-8i)\cdot(7-i) \\ -x\cdot y=(-3)(7)+(-3)(-i)-(8i)(7)+(8i)(i) \\ -x\cdot y=-21+3i-56i+8(i^2) \\ -x\cdot y=-21+3i-56i+8(-1) \\ -x\cdot y=-21-53i-8 \\ -x\cdot y=-29-53i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6jgmpkjoy6dq44xidgd42fotzeyubli69n.png)
Step 4
d)2x-3y
![\begin{gathered} 2x-3y= \\ 2x-3y=2(3+8i)-3(7-i) \\ 2x-3y=6+16i-21+3i \\ 2x-3y=-15+19i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b1culewzxycaycuo2z74lp113v7bjsuzqj.png)
I hope this helps you